A battery-operated portable handheld electrospinning apparatus. Issue 29 (8th July 2015) - Xu, Shi-Cong; Qin, Chong-Chong; Yu, Miao; Dong, Rui-Hua; Yan, Xu; Zhao, Hui; Han, Wen-Peng; Zhang, Hong-Di; Long, Yun-Ze
Abstract : A battery-operated handheld electrospinning apparatus with high safety, good performance and promising application. Abstract : Electrospinning (e-spinning) still has certain limitations in flexible practicability because its conventional setup is usually quite bulky and excessively dependent on a plug (electric supply). In this article, we report on a battery-operated e-spinning apparatus (BOEA) based on miniaturization and integration. The new device gets liberated from the conventional heavy power supply, achieves the tight integration of functional parts and can be operated by a single hand due to its small volume (10.5 × 5 × 3 cm 3 ) and light weight (about 120 g). Different polymers such as polyvinylpyrrolidone (PVP), polycaprolactone (PCL), polystyrene (PS), poly(lactic acid) (PLA) and poly(vinylidene fluoride) (PVDF) were electrospun into fibers successfully, which confirms the stable performance and good real-time control capability of the apparatus. These results demonstrate that the BOEA could be potentially applied in many fields, especially in biomedical fields such as skin damage, wound healing, rapid hemostasis, etc .